Temporomandibular joint injections in dogs with temporomandibular joint pain: 11 cases (2015‐2019). (3rd November 2020) - Almansa Ruiz, J. C.; Kirberger, R. M.; Steenkamp, G.
Abstract : Objectives: To describe and evaluate the clinical application of temporomandibular joint injections using betamethasone and ropivacaine in German Shepherd dogs suffering from non‐odontogenic orofacial pain due to temporomandibular dysplasia and/or osteoarthritis. Materials and Methods: Outcomes in dogs presented with clinical signs of non‐odontogenic orofacial pain associated to temporomandibular joint dysplasia and/or arthritis and treated with a temporomandibular joint injection were retrospectively‐prospectively evaluated. Results: The overall clinical signs free period ranged between 25 to 1579 days, with an average of 461 days. The clinical signs free period for temporomandibular joint osteoarthritis scores 1, 2 and 3 were on average 659 days (180‐1579 days), 134 days (42‐355 days) and 723 days (25‐1377 days), respectively. Similarly the temporomandibular dysplasia scores 1, 2 and 3 were on average 306 days (26‐1579 days), 1377 days and 669 days (25‐1429 days) respectively. Those dogs in which only one side was injected the clinical signs free period average was 639 days (25‐1578 days), compared with dogs in which both temporomandibular joints were injected showing a clinical signs free period average of 378 days (42‐1377 days). Clinical Significance: The temporomandibular joint injection technique proved to be feasible with a decent outcome in dogs suffering from non‐odontogenic orofacial pain associated with temporomandibular joint osteoarthritis and/or dysplasia. Further randomised studies are required to confirm the effectiveness of this intervention.